Regulating Early Biological Events in Human Amniotic Epithelial Stem Cells Using Natural Bioactive Compounds: Extendable Multidirectional Research Avenues - Ferdousi, Farhana; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2022)
Stem cells isolated from perinatal tissue sources possess tremendous potential for biomedical and clinical applications. On the other hand, emerging data have demonstrated that bioactive natural compounds regulate numerous cellular and biochemical functions in stem cells and promote cell migration, proliferation, and attachment, resulting in maintaining stem cell proliferation or inducing controlled differentiation. In our previous studies, we have reported for the first time that various natural compounds could induce targeted differentiation of hAESCs in a lineage-specific manner by modulating early biological and molecular events and enhance the therapeutic potential of hAESCs through modulating molecular signaling. In this perspective, we will discuss the advantages of using naturally occurring active compounds in hAESCs and their potential implications for biological research and clinical applications.